Perancangan dan Implementasi Aplikasi Pendaftaran Online PORKOTA Berbasis Client Server Menggunakan Web dan Android - Ariyanti, Dyah (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Comitte nasional sports of Indonesia is the organization that focus on sport. Every two years, Probolinggo's KONI hold city sports week activity that specially for elementary and junior hight school students. In every registration process Porkota's participant currently it is still done manually which causes the registration process to occur a lot of error and requirs a longer time. Along with the development of technology, an online registration system is needed to simplify the registration process and prevent errors from occurring. The PORKOTA registration application consists of web and android applications. The android application is used by the school to register and the web application is used by KONI to make data changes, delete data and print data. Design of PORKOTA registration process system is described in the Unified Modeling Language (UML). Then develop a client server based application using web and android with the System Development Life Cycle (SDLC) method as a solution to these problems. The results of this study is the creation of a client server-based PORKOTA online registration application using web and android. This application is expected to help the school and the Probolinggo's KONI in facilitating the PORKOTA registration process